Relato da experiência de 9 anos do Centro de Oncologia Bucal (COB) FOA/UNESP em um programa de prevenção para o câncer de boca em pacientes tabagistas crônicos - Rosa, Felipe de Mello [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Oral cancer is a growing problem in many parts of the world, resulting in high morbidity and mortality. Chronic consumption of tobacco and alcohol are the main risk factors for developing the disease. Early-stage oral cancer is often asymptomatic and early detection plays a key role in controlling the disease. Therefore, the extension project “Educational actions for the prevention of oral cancer in a population at risk” was developed to offer clinical examination (anamnesis, extra and intraoral physical examination) with the aim of early detection of potentially malignant oral disorders and the oral cancer, in addition to providing guidance on risk factors, signs and symptoms of the disease. The objective of this study is to report the experience of the Oral Oncology Center (COB) regarding the activities carried out by the extension project in a prevention program for oral cancer in current smokers and/or alcoholics patients between the years 2014 and 2022. The actions were developed by the COB of the Faculty of Dentistry of Araçatuba (FOA-UNESP) together with partner Municipal Health Centers in Araçatuba and the region. The project activities were developed by professors, postgraduate students and undergraduate dentistry students. In total, 353 patients who were chronic smokers and/or alcoholics were treated. 303 lesions were observed, of which 270 (89%) were benign and 33 (11%) were potentially malignant oral disorders. Among the potentially malignant disorders, 21 (64%) patients had leukoplakia, 8 (24%) had actinic cheilitis, 3 (9%) erythroplakia and 1 (3%) patient had erythroleukoplakia. One of the patients with a clinical diagnosis of erythroplakia was referred for clinical care at COB and underwent a biopsy whose histopathological results revealed the diagnosis of squamous cell carcinoma. Therefore, it is concluded that this program developed by COB, through the extension project, had the capacity to enhance the early diagnosis of potentially malignant oral disorders and oral cancer. Furthermore, the project provided the training of future professionals, transmitting knowledge and clinical training, as well as generating data for scientific studies on oral cancer prevention. Finally, the development of the project “Educational actions for the prevention of oral cancer in a population at risk” promotes the visibility of COB, FOA and UNESP among public health institutions and society involved in the detection of potentially potentially harmful oral disorders. malignant diseases, oral cancer and early start of their treatments.

Oral cancer is a growing problem in many parts of the world, resulting in high morbidity and mortality. Chronic consumption of tobacco and alcohol are the main risk factors for developing the disease. Early-stage oral cancer is often asymptomatic and early detection plays a key role in controlling the disease. Therefore, the extension project “Educational actions for the prevention of oral cancer in a population at risk” was developed to offer clinical examination (anamnesis, extra and intraoral physical examination) with the aim of early detection of potentially malignant oral disorders and the oral cancer, in addition to providing guidance on risk factors, signs and symptoms of the disease. The objective of this study is to report the experience of the Oral Oncology Center (COB) regarding the activities carried out by the extension project in a prevention program for oral cancer in current smokers and/or alcoholics patients between the years 2014 and 2022. The actions were developed by the COB of the Faculty of Dentistry of Araçatuba (FOA-UNESP) together with partner Municipal Health Centers in Araçatuba and the region. The project activities were developed by professors, postgraduate students and undergraduate dentistry students. In total, 353 patients who were chronic smokers and/or alcoholics were treated. 303 lesions were observed, of which 270 (89%) were benign and 33 (11%) were potentially malignant oral disorders. Among the potentially malignant disorders, 21 (64%) patients had leukoplakia, 8 (24%) had actinic cheilitis, 3 (9%) erythroplakia and 1 (3%) patient had erythroleukoplakia. One of the patients with a clinical diagnosis of erythroplakia was referred for clinical care at COB and underwent a biopsy whose histopathological results revealed the diagnosis of squamous cell carcinoma. Therefore, it is concluded that this program developed by COB, through the extension project, had the capacity to enhance the early diagnosis of potentially malignant oral disorders and oral cancer. Furthermore, the project provided the training of future professionals, transmitting knowledge and clinical training, as well as generating data for scientific studies on oral cancer prevention. Finally, the development of the project “Educational actions for the prevention of oral cancer in a population at risk” promotes the visibility of COB, FOA and UNESP among public health institutions and society involved in the detection of potentially potentially harmful oral disorders. malignant diseases, oral cancer and early start of their treatments.
Report of the 9-year experience of the Oral Oncology Center (COB) FOA/UNESP in a prevention program for oral cancer in chronic smokers
Keywords: Câncer; Boca Tumores; Leucoplasia bucal; Cancer Prevenção; Diagnóstico precoce; Early diagnosis